Biomimetic Synthesis of Materials for Technology. Issue 27 (12th June 2013) - Galloway, Johanna M.; Bramble, Jonathan P.; Staniland, Sarah S.
Abstract In a world with ever decreasing natural reserves, researchers are striving to find sustainable methods of producing components for technology. Bioinspired, biokleptic and biomimetic materials can be used to form a wide range of technologically relevant materials under environmentally friendly conditions. Here we investigate a range of biotemplated and bioinspired materials that can be used to develop components for devices, such as optics, photonics, photovoltaics, circuits and data storage.